Health related quality of life in paediatric spina bifida - Thong, P. L.; Wong, S. W.; Abdul Manaf, M. R.; Lee, M. L.; Kanaheswari, Y. (Malaysian Medical Association, 2019)
Introduction: The average incidence of spina bifida (SB) in Malaysia is 0.43 among 1,000 live births. The burden of the disease and its impact on the overall development and health though tremendously improved, remains significant. Therefore, current patient management strategies must include quality of life (QOL) measures. Methods: This was a prospective, cross-sectional study on spina bifida children aged 5-20 years, attending the paediatric spina bifida clinics of Universiti Kebangsaan Malaysia Medical Centre Kuala Lumpur and Hospital Tuanku Jaanku Seremban. Scores were obtained using the validated disease specific Parkin QOL questionnaire. Univariate and multivariate analysis were used to investigate factors that were determinants for these outcomes. Results were expressed as beta coefficient and 95% confidence intervals (95%CI). Results: A total of 54 children and adolescents aged between 5-20 years completed the questionnaires. Presence of neurogenic bowel (p=0.003), neurogenic bladder (p=0.041), shunt (p=0.044), non-ambulators (p=0.007) and being the only child in the family (p=0.037) were associated with lower QOL scores. Multivariate analysis showed presence of neurogenic bowel (β=0.375, 95%CI: 0.00, 0.15) and being the only child in the family (β=0.250, 95%CI: 0.04, 0.17) explained 22.1% of the variance in the QOL mean percentage scores. Conclusion: Being a single child in the family was the only socio-demographic variable associated with lower QOL scores. Although several clinical factors appeared to contribute significantly to QOL in spina bifida children, the presence of neurogenic bowel had the greatest impact.